Effect of foot massage on Nausea, Vomiting and Retching in women with cervical cancer undergoing chemotherapy, in Bali, Indonesia - Ni Ketut Guru Prapit (Prince of Songkla University, 2013)
Thesis (M.N.S., Nursing Science)--Prince of Songkla University, 2012